The effect of a currency board arrangement on subjective assessments of a country's economic performance. (18th January 2023) - Begović, Selena; Adnett, Nick; Pugh, Geoff
We present a novel approach to evaluating the effect of a monetary exchange rate regime on economic performance, focusing on countries with a currency board arrangement (CBA). This approach is designed to evaluate the impact of the regime on the perceptions and expectations of a population. We utilise seemingly unrelated regressions to analyse data from large-sample surveys conducted by the Austrian National Bank over the period 2007-2016 in ten European transition economies. The analysis indicates that the probability of the economic situation in a country being perceived as good by its citizens is lower in countries with a currency board arrangement. However, this negative effect almost disappears among respondents who do not trust their government and when there is a significant recession in the country. These findings suggest that a CBA should be maintained for its stabilising effects: 1) when the economic situation is unfavourable, although it might not be beneficial once the situation is stabilised; 2) in countries with low levels of trust in government.